High Fidelity Nursing Using Electronic Health Record Systems: Impact on Critical Thinking in Nursing Practice - Miller, Michele L. (My University, 2019)
Since Florence Nightingale changed the way the world viewed nursing, the nursing profession has continued to advance and change daily. It can be challenging for nurses to keep up with changes in policies, standards, and advances in nursing technology. This is also a challenge for nursing programs. One thing that has not changed in the nursing education field is the need for students to have proficient critical thinking skills. Durmaz Edeer & Dicle, (2015) stated, “proficiency in thinking skills is an essential requirement of today’s nurses who are having to make knowledgeable, confident, and effective decisions regarding health in a complex and changing environment” (p. 2). Teaching documentation using the nursing process and paper-based documents has been instrumental in helping students develop critical thinking, clinical reasoning and clinical judgement. The mandate of Electronic Health Record System placed on Healthcare facilities created an added challenge for nursing programs to transition to the new system while continuing to help student develop critical thinking skills. The purpose of this study was to determine if the implementation of electronic health records system into nursing programs had an impact on the development of Associate Degree nursing student’s critical thinking skills. The theoretical frameworks by Paul & Elder, Blooms taxonomy and the nursing process used in this study supported the nursing program’s curriculum for teaching critical thinking, clinical reasoning and judgement skills. A causal-comparative research design was used to explore the relationship between student’s critical thinking scores and the type of documentation taught at the Associate Degree nursing level. Archived data was collected from the Clinical Judgement and Clinical Reasoning & Critical Thinking section of the Health Education Systems, Inc (HESI) exams. Analysis of the data included are the Wilcoxon test, Mann-Whitney U test, and Kruskal-Wallis H test, and ANCOVA. The independent variable was the type of documentation students were taught in their perspective programs. The dependent variables were exam scores from the section of the HESI exams for Clinical Judgement and Clinical Reasoning & Critical thinking. When the Fundamental scores were incorporated as a covariate, the results revealed there was an impact on critical thinking of student taught with Electronic Health Records.
CHAPTER I: INTRODUCTION 1 -- Statement of Problem 5 -- Purpose of Study 6 -- Significance of Study 8 -- Theoretical Framework 10 -- Summary of Methodology 15 -- Study Limitations 16 -- Definition of Terms 17 -- Summary 19 -- CHAPTER II: REVIEW OF LITERATURE 20 -- Introduction 20 -- Electronic Health Record System 20 -- Healthcare Facility Experiences with EHRS Documentation 23 -- Nurse Faculty and Program Experiences with EHRS 24 -- Student Experiences with EHRS 28 -- Critical Thinking and Clinical Decision Making 31 -- Summary 34 -- CHAPTER III: METHODOLOGY 36 -- Introduction 36 -- Research Design 37 -- Methods 41 -- Data Collection and Management 42 -- Instrumentation 42 -- Summary 48 -- REFERENCES 75 -- APPENDIX A 85 -- APPENDIX B 88 -- APPENDIX C 90.
Keywords: Dissertations, Academic--United States; Medical records--Data processing; Critical thinking; Nursing students